An adaptable business component based on pre-defined business interfaces - Pereira, Óscar Narciso Mortágua
Object-oriented and relational paradigms are simply too different to bridge seamlessly. Architectures of database applications relying on three tiers need business tiers to bridge application tiers and database tiers. Business tiers hide all the complexity to convert data between the other two tiers easing this way programmers’ work. Business tiers are critical components of database applications not only for their role but also for the effort spent on their development and their maintenance. In this paper we propose an adaptable business component (ABC) able to manage SQL statements on behalf of other components. Other components may create in run-time a pool of SQL statements of any complexity and delegate their management to the ABC component. The only constraint is that the SQL statements schema must be in conformance with one of the predefined schemas (interfaces) provided by the ABC component. The main contribution of this paper is twofold: 1) the presentation of an adaptable business component and 2) to show that the ABC source code may be automatically generated. The main outcome of this paper is the evidence that the ABC component is an effective alternative approach to build business tiers to bridge object-oriented and relational paradigms.